Eksistensi Komunitas Perupa Lombok dalam Pengembangan Seni Lukis - aswandi mahroni; Mi'rajus Subyan Rahmat (Universitas Bumigora, 2021)
The development of Lombok's fine arts develops along with the existence of artists in their awareness of work. The existence of the artist is to balance the space so that it becomes a good public lesson for the general public and the generation of artists in particular. The existence of art becomes a forum for the running of the community in a certain scope, therefore it is expected to be the main learning when the amount of formal education is limited. This study seeks to find data on the development of the visual arts community in Lombok as well as an effort to develop literature related to fine art references. The existing community will be a reference for comparison in all forms of activity and archive of artistic activities in each period. The research uses an approach and data analysis approach to determine the existence of developments in art activities through the objectives and planning of visual arts activities. The results of the study show that the visual arts community in Lombok is influenced by the existence of formal and non-formal institutions that are spaces for developing creativity. The number of communities that are formed and active in the activity agenda is still minimal and other art activities are limited to the annual agenda.